Base Erosion Profit Shifting BEPS Pillar Two: An Accounting Challenge - Marta MAZUROWSKA (Communications of International Proceedings, 2023)
The purpose of the article is to discuss the matter of Pillar Two Regulations and it’s influence on disclosures in financial statement. Pillar Two Regulations are extremely difficult tax regulation, which will influence multinational companies dinancial situation, what should be clearly presented in financial reports.
Keywords: accounting; Pillar Two; BEPS; disclosures